Studi Komparasi Karakteristik Gelombang Pesisir Barat Lampung - Hermanto, Mochammad Fathurridho; Nandalianadhira, Nafisa; Kencana, Elsa Rizkiya; Sari, Shila Atika; Apriliyani, Ulan; Pardede, Ida Juliana; Setiono, Fadlillah Ihsan; Wulandari, Eka Suci Puspita (Departemen Teknik Kelautan Universitas Hasanuddin, 2024)
The need for ocean data is important to increase the utilization of ocean areas. A facility, development, system, or structure in the ocean cannot be planned properly without data in that ocean. One of the important data in water areas is ocean waves. In the offshore area of Pesisir Barat, wave characteristic data is still very hard to find. Knowledge of the ocean characteristics of the Pesisir Barat waters is needed, one of which is in the form of wave characteristics. To obtain more comprehensive information, two satellite reanalysis data sources were analyzed. The average height of significant wave height in the Perisir Barat is 1.75 to 2.25 m from BMKG and only 0.25 to 1.00 m from ECMWF. Based on the wave direction, the ocean waves in the Pesisir Barat move North to Northwest (NW), perpendicular to the coastline. The distribution of the annual maximum significant wave height matches the theoretical Log-normal distribution. Extreme significant wave height is obtained with a value of 4.10 to 4.29 m for a 100-year return period and 3.09 to 3.39 m for a 1-year return period. In terms of design or study of maritime potential in the western waters of Lampung, these values can be a benchmark as a basic study of wave characteristic data.